KKN TEMATIK UNTIRTA : PELATIHAN PEMBUATAN NATA DE COCO DAN PELATIIHAN DIGITAL MARKETING DI DESA RAMAYA KECAMATAN MENES KABUPATEN PANDEGLANG - Rahmawati Rahmawati; Abdul Apip; M Ikhlas Rury D; Alysa Citrifolia Budi Ramansyah (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2022)
Student Work Lecture is a form of community service carried out by universities through student activities as part of the course. The form of PT's contribution to the problems faced by the community through KKM activities as an effort to get closer to PT and also make students as agents of change change and community empowerment. KKM Regular 1 Untirta is carried out still in the Covid-19 pandemic situation, where this pandemic has a very significant impact on all aspects of people's lives, especially in the economic sector and community welfare. The impact is in the form of job cuts, limited employment of other workers, and for people who have businesses or act as sellers, there is a decrease in sales turnover. This is the background in the regular KKM 1 Untirta activities in Ramaya Village, Menes District, Pandeglang Regency, education is carried out to the community through nata de coco manufacturing training activities and digital marketing training through market places to the community. Ramaya Villagers mostly work in the agricultural sector where Ramaya Village has the potential for plantation products in the form of coconuts, palm trees and abundant melinjo fruit, for coconut fruit itself has not been optimized for its benefits, only limited to utilization for cooking needs in the household. Educational activities by the KKM 1 Group are carried out gradually, for phase 1 in the form of digital marketing training education activities and stage 2 training in making nata de coco from coconut water. From the results of these educational activities, it is hoped that the people of Ramaya Village can take advantage of the potential of coconut water into food that can be traded through simple marketing and can increase through digital marketing in the market place